2018
DOI: 10.1094/pbiomes-09-17-0042-r
|View full text |Cite
|
Sign up to set email alerts
|

Root-Associated Bacterial and Fungal Community Profiles ofArabidopsis thalianaAre Robust Across Contrasting Soil P Levels

Abstract: Plant survival depends on the ability of roots to sense and acquire nutrients in soils, which harbor a rich diversity of microbes. A subset of this microcosm interacts with plant roots and collectively forms root-associated microbial communities, termed the root microbiota. Under phosphorus-limiting conditions, some plants can engage in mutualistic interactions, for example with arbuscular mycorrhizal fungi. Here, we describe how Arabidopsis thaliana, which lacks the genetic capacity for establishing the afore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…Although the composition of the root microbiota has been shown to be strongly dependent on the soil in which the plant grows (Peiffer et al ., ; Schlaeppi et al ., ), the mechanistic basis underlying the control of root‐associated microbial communities by soil nutrient availability is largely unknown. Recent reports on A. thaliana root microbiota revealed a higher impact of long‐term soil fertilization with P on fungal communities compared with bacteria (Robbins et al ., ). In this article, we significantly expanded this knowledge by studying how P availability in natural nonsterile soil and the plant's response to soil P (controlled by the PSR) jointly shape the root‐associated fungal microbiota of the AM nonhost species A. thaliana in the short term.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although the composition of the root microbiota has been shown to be strongly dependent on the soil in which the plant grows (Peiffer et al ., ; Schlaeppi et al ., ), the mechanistic basis underlying the control of root‐associated microbial communities by soil nutrient availability is largely unknown. Recent reports on A. thaliana root microbiota revealed a higher impact of long‐term soil fertilization with P on fungal communities compared with bacteria (Robbins et al ., ). In this article, we significantly expanded this knowledge by studying how P availability in natural nonsterile soil and the plant's response to soil P (controlled by the PSR) jointly shape the root‐associated fungal microbiota of the AM nonhost species A. thaliana in the short term.…”
Section: Discussionmentioning
confidence: 97%
“…; Tables S6, S7). This contrasts with long‐term fertilization studies, which have reported shifts in fungal soil communities on long‐term amendment of the soil with P fertilizer (Leff et al ., ; Robbins et al ., ), and suggests that P fertilization exerts rapid effects specifically on root‐associated microbes. It is also possible that short‐term effects of P concern primarily the activity of soil fungi, rather than their presence or abundance; therefore, RNA‐ rather than DNA‐based fungal community studies are needed to account for these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root-specific enrichment for widespread OTUs, compared to soil and RS samples was tested with a generalized linear model, as described in ref. 22 (FDR, p < 0.05). To compare generalist OTUs from this study with OTUs found in roots of Lotus japonicus 26 bacterial OTUs were directly compared using the representative sequences (Blastn, 98% sequence identity).…”
Section: Methodsmentioning
confidence: 98%
“…However, the relative importance of different abiotic and biotic factors for the evolution and maintenance of local adaptation is poorly known 17, 18 . Particularly, soil edaphic factors and soil microbes are known to influence flowering phenology and modulate host fitness in natural soils 19, 20, 21, 22, 23 , even at the scale of a few meters 24 . Yet, information about the extent to which differences in soil properties contribute to divergent selection and the maintenance of adaptive differentiation among plant populations is still limited beyond classical examples of adaptation to extreme soil conditions 25 .…”
Section: Introductionmentioning
confidence: 99%